Treatment Outcomes and Prognostic Factors of Patients With Primary Spinal Ewing Sarcoma/Peripheral Primitive Neuroectodermal Tumors - Chen, Jun; Li, Mengxue; Zheng, Yifeng; Zheng, Lei; Fan, Fanfan; Wang, Yu (Frontiers in Oncology, 2019)
Purpose: Primary spinal Ewing sarcoma (ES)/peripheral primitive neuroectodermal tumors (pPNETs) are extremely rare, and the current understanding of these tumors is poor. The authors aimed to illustrate the clinical characteristics of primary spinal ES/pPNETs and to discuss prognostic factors by survival analysis. Methods: A total of 40 patients who were pathologically diagnosed with primary spinal ES/pPNETs between 2000 and 2018 were enrolled in this study. Progression-free survival (PFS) and overall survival (OS) were estimated by the Kaplan–Meier method to identify potential prognostic factors. Factors of p values ≤ 0.1 in the Log-rank tests were subjected to multivariate analysis by Cox regression analysis. Results: The mean follow-up period was 23.8 (range, 2–93) months, and 24 (60.0%) patients had local recurrence and 11 (27.5%) patients had distant metastasis. The one-, two-, and five-year PFS rates were 57.7%, 30.4%, and 9.5%, respectively. The one-, two-, and five-year OS rates were 74.8%, 50.7%, and 12.2%, respectively. The univariate analysis suggested that resection mode, postoperative Frankel score, adjuvant chemotherapy and adjuvant radiotherapy were potential prognostic factors for OS and PFS. However, after these factors were subjected to multivariate analyses, only adjuvant radiotherapy and resection mode remained as independent prognostic factors. Conclusions: Total en bloc resection can significantly improve PFS for primary spinal ES/pPNETs and adjuvant radiotherapy was a favorable factor for PFS. Total en bloc resection and adjuvant radiotherapy considerably improve OS for patients with primary spinal ES/pPNETs.